An integrated system for the management of environmental data to support veterinary epidemiology - Mazzucato, Matteo; Marchetti, Giulio; Barbujani, Marco; Mulatti, Paolo; Fornasiero, Diletta; Casarotto, Claudia; Scolamacchia, Francesca; Manca, Grazia; Ferrè, Nicola (Frontiers in Veterinary Science, 2023)
Environmental and climatic fluctuations can greatly influence the dynamics of infectious diseases of veterinary concern, or interfere with the implementation of relevant control measures. Including environmental and climatic aspects in epidemiological studies could provide policy makers with new insights to assign resources for measures to prevent or limit the spread of animal diseases, particularly those with zoonotic potential. The ever-increasing number of technologies and tools permits to acquire environmental data from various sources, including ground-based sensors and Satellite Earth Observation (SEO). However, the high heterogeneity of these datasets often requires at least some basic GIS and/or coding skills to use them in further analysis. Therefore, the high availability of data does not always correspond to widespread use for research purposes. The development of an integrated data pre-processing system makes it possible to obtain information that could be easily and directly used in subsequent epidemiological analyses, supporting both research activities and the management of disease outbreaks. Indeed, such an approach allows reducing the time spent on searching, downloading, processing and validating environmental data, thereby optimising available resources and reducing any possible errors directly related to data collection. Although multitudes of free services that allow obtaining SEO data exist nowadays (either raw or pre-processed through a specific coding language), the availability and quality of information can be sub-optimal when dealing with very small scale and local data. In fact, some information sets, usually derived from ground-based sensors, are managed, processed and redistributed by agencies operating on a local scale which are often not directly accessible by the most common free SEO services (e.g. Google Earth Engine). The EVE (Environmental data for Veterinary Epidemiology) system has been developed to acquire, pre-process and archive a set of environmental information at various scales, in order to facilitate and speed up access to climate data by epidemiologists, researchers and decision-makers, also accounting for the integration of SEO information with locally sensed data.